Evaluation of Blended Learning in the Sports Education Masters Program at State University of Malang Using the Cipp Model - Aprilius Bayu; Mashuri Eko Winarno (CV. SAMODRA INSAN PENA, 2025)
This study evaluates the implementation of blended learning in the Master’s Program of Sports Education at Universitas Negeri Malang using the CIPP evaluation model. The growing integration of digital technology in higher education necessitates a comprehensive assessment of contextual readiness, resource quality, instructional processes, and learning outcomes. The purpose of this study is to provide a complete overview of the program’s effectiveness and identify components that require improvement. A descriptive evaluation approach was employed, utilizing a 16-item instrument representing the four CIPP elements. Data were collected from 16 students through a structured questionnaire and analyzed using descriptive statistics. The results indicate that the blended learning program falls within the “good” category, with consistent performance across context, input, process, and product components. However, several technical aspects and interaction patterns require further enhancement. Overall, blended learning has proven relevant and effective for postgraduate education, yet continuous evaluation is needed to further strengthen its quality.